Developing A Digital Marketing Strategy to Enhance Product Sales and Brand Awareness: A Case Study of Sentraloka Indonesia - Nur, Ibrahim Muhammad; Dalimunthe , Gallang Perdhana (Journal of Economics and Business UBS, 2026)
This study examines the challenges of Sentraloka Indonesia, a digital retail intermediary of MSME snack products, which is facing sales stagnation and weak brand awareness. Companies rely too heavily on short-term paid advertising, resulting in revenue volatility and a lack of organic demand. Fragmented digital communication limits the formation of a coherent brand identity. The research uses an integrated framework: Resource-Based View (RBV) and VRIO for internal analysis, Porter's Five Forces for external pressures, and SWOT and TOWS to generate strategic alternatives based on Integrated Marketing Communication (IMC) in an omnichannel perspective. The main premise is that Sentraloka has valuable intangible resources—market reputation and relationships with MSME suppliers—that have the potential to generate Sustainable Competitive Advantage but are underutilized due to the weakness of the Organizational (O) dimension. The research design was a qualitative single case study with in-depth interviews of three internal stakeholders and ten external informants, analyzed using Braun and Clarke's reflective thematic analysis. The findings reveal that although Sentraloka's resources meet the criteria of Value, Scarcity, and partial Inadmissibility, the company falls short on the Organization dimension due to manual systems, inconsistent content, and the absence of a structured CRM. The proposed IMC strategy emphasizes three pillars: strengthening brand credibility, differentiating MSME storytelling, and CRM-based recurring engagement, implemented through a 12-month phased plan. Contributions include a managerial roadmap for the transition of MSMEs from promotion-based sales to sustainable growth, as well as a theoretical expansion of IMC's literature by demonstrating its role as a strategic organizational integrator to transform intangible resources into sustainable competitive advantages.